Examination and genetic analysis of a yellow‐green leaf mutant a269 of sweetpotato. (4th December 2019) - Luo, Zhongxia; Zhang, Xiongjian; Chen, Jingyi; Wang, Zhangying; Huang, Lifei; Zou, Hongda; Yao, Zhufang; Yang, Yiling; Fang, Boping
Abstract: The genetic behaviour of a yellow‐green leaf sweetpotato mutant, a269, was analysed to prepare for genetic mapping and cloning of this mutant and to elucidate the regulation of its molecular mechanisms. The phenotypic stability of the mutant was observed under natural conditions, and photosynthetic pigments in mature leaves were measured. GN1323 and a269 were crossed and backcrossed. Genetic behaviour was assessed using phenotypic expression and segregation in F1, BC1 and BC2 . The a269 leaves were yellow‐green at all stages after germination. The thylakoid lamellae of a269 were disorganized, had incomplete grana and were fewer compared with GN1323. The direct and reciprocal F1 populations had normal leaf colour, whereas the BC2 populations had yellow‐green leaves. Segregation of plants with normal‐ and yellow‐green leaf colour in the four BC1 populations satisfied the backcross segregation ratio of 11 : 1 for auto‐allohexaploids. The a269 mutant is stable, and its trait is controlled by one recessive nuclear locus.